THE COSMOCHEMICAL BEHAVIOR OF BERYLLIUM AND BORON - Lauretta D.S.; Lodders K. (My University, 1997)
The chemistry of Be and B in the solar nebula is reinvestigated using thermodynamic equilibrium calculations. The dominant Be gases are monatomic Be at high temperatures and the hydroxides BeOH and Be(OH)2 at lower temperatures. Beryllium condenses as gugiaite (Ca2BeSi2O7) in solid solution with melilite with a 50% condensation temperature of 1490 K. If an ideal solid solution of chrysoberyl (BeAl2O4) into spinel is assumed, most of the Be condenses into spinel, yielding a 50% condensation temperature of 1501 K. However, the difference in the crystal structures of spinel and chrysoberyl indicates that their solid solution may be non-ideal. At high temperatures the dominant B gases are BO, HBO, and HBO2, while NaBO2, KBO2, and LiBO2 are dominant at lower temperatures. Boron is less refractory than Be and is calculated to condense into solid solution with feldspar. The majority of B condenses as danburite (CaB2Si2O8) in solid solution with anorthite. At lower temperatures, when the feldspar composition is more albitic, the remaining B condenses as reedmergnerite (NaBSi3O8). The 50% condensation temperature of B is 964 K. The 50% condensation temperature of B is similar to that of Na and much higher than that of S. Therefore, normalized B abundances in chondrites are expected to correlate with Na abundances. Be is predicted to be concentrated in melilite, a conclusion which is consistent with the few measurements of Be concentrations in calcium aluminum-rich inclusions (CAIs). Boron is predicted to be concentrated in feldspar, but no analytical data are available to test this prediction.
Keywords: CONDENSATION; SOLAR NEBULA; BERYLLIUM; BORON